Filling knowledge gaps: A methodological approach for the rapid investigation of species with restricted populations - André Cesar Furlaneto Sampaio; Pablo Melo Hoffmann; Elivelton Marcos Gurski; Ollyver Rech Bizarro; Santiago José Elías Velazco; Marcos Bergmann Carlucci; Marília Borgo; Mayara Monteiro Ferreira; Alessandro Camargo Angelo; Christopher Thomas Blum (Perspectives in Ecology and Conservation)
Gaps in geographic, genetic, and ecological data persist for many plant species, particularly those with restricted populations that are often rare and endangered. This lack of data hampers conservation efforts, especially in regions facing rapid habitat degradation and limited research investment. Additionally, technological, methodological, financial, and governmental challenges further hinder data collection. To address this issue, we developed the Multi-Scale Habitat and Population Rapid Assessment (MHPR) methodology, integrating widely tested, low-cost, and rapid-application technologies to assess distribution, demography, and population decline risks in species with restricted populations. We applied this approach to Butia pubispatha, a critically endangered dwarf palm endemic to the southern Brazilian grasslands, known from a single recorded population. In the first phase, we used Landsat satellite imagery and the Normalized Difference Vegetation Index (NDVI) to analyze habitat degradation between 2013 and 2021. Using landscape ecology principles, we identified the focal habitat patch with the highest potential to support the species. In the second phase, we conducted systematic transects and distance sampling within this area, mapping the population and identifying less degraded sectors. The highest-density sector was censused. In the third phase, we analyzed spatial patterns using Morisita’s Index and Ripley’s K function. Our method proved highly effective and replicable. NDVI successfully detected habitat changes over time, revealing an 86.7% reduction in the focal habitat patch from 2013 to 2021, underscoring the species’ critical threat due to habitat degradation. We recorded 1,615 individuals, with an estimated density of 81.2 in/ha and a dispersal range of 145 m. A second population was identified in this study. Our findings provide key insights for phenological studies, seedling production, genetic research, and public policies aimed at establishing protected areas and translocating individuals for the conservation of Butia pubispatha.